(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This investigation exhibits removal of phenol from aqueous solution utilizing the carbons arranged from the normal sources, i.e., olive-pit, date-pit, and pomegranate-piece in a batch framework. For correlation reason, the adsorption tests were likewise completed on a commercial activated carbon. Phenol is a natural contamination the present examination was led to look at the adsorption of phenol. Level of expulsion of phenol expanded as the adsorbent portion increment. Level of evacuation of phenol expanded as the adsorbent portion increment.